2019
DOI: 10.1186/s12876-018-0923-7
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effect of ecabet sodium on low-dose aspirin-induced small intestinal mucosal injury: a randomized, double-blind, pilot study

Abstract: BackgroundWe aimed to investigate how high-dose ecabet sodium affects low-dose aspirin-induced small intestinal mucosal injury in healthy volunteers.MethodsHealthy volunteers were enrolled randomly into one of two groups with the following drug regimens for 2 weeks: group A, low-dose aspirin once per day and group B, low-dose aspirin and 4.0 g of ecabet sodium. Small bowel capsule endoscopy was performed before and 2 weeks after low-dose aspirin administration.ResultsA significant difference was found in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
0
12
0
1
Order By: Relevance
“…Rebamipide 49,50 and irsogladine 50,51 have demonstrated superiority to placebo in both prevention and treatment of NSAID-induced enteropathy, whereas polaprezinc showed efficacy only in ulcer healing 52 and teprenone (geranylgeranylacetone) 53 and ecabet sodium only in prevention. 54 Nevertheless, none of these medications have been proven to be effective in SB bleeding ulcers outside of misoprostol. 19 ' 48…”
Section: Approach To Treatment and Preventionmentioning
confidence: 99%
“…Rebamipide 49,50 and irsogladine 50,51 have demonstrated superiority to placebo in both prevention and treatment of NSAID-induced enteropathy, whereas polaprezinc showed efficacy only in ulcer healing 52 and teprenone (geranylgeranylacetone) 53 and ecabet sodium only in prevention. 54 Nevertheless, none of these medications have been proven to be effective in SB bleeding ulcers outside of misoprostol. 19 ' 48…”
Section: Approach To Treatment and Preventionmentioning
confidence: 99%
“…Studies using capsule endoscopy have shown that rebamipide also prevented both NSAIDs-and LDA-induced enteropathy in healthy volunteers [22,115] and promoted the healing of intestinal mucosal breaks in chronic users of NSAIDs and LDA [116,117]. Other muco-protective drugs such as irsogladine [118], polaprezinc [119], geranylgeranylacetone [120], and ecabet sodium [121] have demonstrated their therapeutic potential for NSAIDs/LDA-induced enteropathy. However, similar to other drugs besides misoprostol, none of these muco-protective drugs have been proven to be effective on clinically significant small intestinal injuries (Table 2).…”
Section: Gastric Muco-protective Drugsmentioning
confidence: 99%
“…Apart from the above agents, there are several other drugs such as sulphasalazine, 42 ecabet sodium, 43 egualen sodium, 44 curcumin, 95,96 and muscovite, 45 which were reported to have a preventive effect on NSAIDs-induced small intestine injury. However, data is very limited for these agents.…”
Section: Othermentioning
confidence: 99%